Maize distillers dried grains with solubles alter dietary digestibility and improve intestine health of pacu, Piaractus mesopotamicus juveniles - Batista Oliveira, Katia Rodrigues [UNESP]; Peres, Helena; Oliva-Teles, Aires; Marconi, Joana Nize; Paulino, Renan Rosa; Diogenes, Alexandre Firmino; Macedo Viegas, Elisabete Maria (Cambridge Univ Press, 2021)
Two trials were conducted to evaluate the effects of soyabean meal replacement by maize distillers dried grains with solubles (DDGS) in diets for pacu juveniles. Five diets were formulated with 0, 100, 200, 300 and 400 g of DDGS/kg diet replacing up to total dietary soyabean meal. In trial 1, the experimental diets were fed to five groups of fish to evaluate the apparent digestibility coefficients (ADC). In trial 2, four groups of fish were fed each experimental diet for 100 d to evaluate the effects of these diets on digestive enzyme activity, intestine oxidative stress and intestine morphology. The ADC of DM and energy was reduced with dietary DDGS inclusion, while the ADC of lipids was increased, and no differences were observed for the ADC of protein. Independent of dietary treatment, pH increased from anterior to the distal intestine with dietary DDGS inclusion. Digestive enzyme activities were higher on anterior than the distal intestine. Dietary DDGS decreased lipase, amylase, chymotrypsin and trypsin activities, while no differences were observed for total protease activity. Intestine glucose-6-phosphate dehydrogenase was reduced in fish fed the DDGS diets, while catalase activity increased. Lipid peroxidation was lower in fish fed DDGS diets than the control. Intestine histomorphology improved with dietary DDGS inclusion. Overall, the negative effects of soyabean meal could be decreased by dietary replacement with maize DDGS which may have a prebiotic effect, improving intestine health.
Keywords: Antioxidant capacity; Digestibility; Digestive enzymes; Intestine health; Prebiotics